A tale of two habitats: Bacteroides fragilis, a lethal pathogen and resident in the human gastrointestinal microbiome. Issue 4 (11th April 2022) - Patrick, Sheila
Abstract : Bacteroides fragilis is an obligately anaerobic Gram-negative bacterium and a major colonizer of the human large colon where Bacteroides is a predominant genus. During the growth of an individual clonal population, an astonishing number of reversible DNA inversion events occur, driving within-strain diversity. Additionally, the B. fragilis pan-genome contains a large pool of diverse polysaccharide biosynthesis loci, DNA restriction/modification systems and polysaccharide utilization loci, which generates remarkable between-strain diversity. Diversity clearly contributes to the success of B. fragilis within its normal habitat of the gastrointestinal (GI) tract and during infection in the extra-intestinal host environment. Within the GI tract, B. fragilis is usually symbiotic, for example providing localized nutrients for the gut epithelium, but B. fragilis within the GI tract may not always be benign. Metalloprotease toxin production is strongly associated with colorectal cancer. B. fragilis is unique amongst bacteria; some strains export a protein >99 % structurally similar to human ubiquitin and antigenically cross-reactive, which suggests a link to autoimmune diseases. B. fragilis is not a primary invasive enteric pathogen; however, if colonic contents contaminate the extra-intestinal host environment, it successfully adapts to this new habitat and causes infection; classically peritoneal infection arising from rupture of an inflamed appendix or GI surgery, which if untreated, can progress to bacteraemia and death. In this review selected aspects of B. fragilis adaptation to the different habitats of the GI tract and the extra-intestinal host environment are considered, along with the considerable challenges faced when studying this highly variable bacterium.